Impact of osteopathic therapy on proprioceptive balance and quality of life in patients with dizziness. Issue 4 (October 2017) - Papa, L.; Amodio, A.; Biffi, F.; Mandara, A.
Abstract: The aim of the study was to evaluate the efficacy of osteopathic manipulative treatment (OMT) in patients with Benign-Paroxysmal-Positional Vertigo (BPPV). Thirty-one patients with BPPV were randomly assigned into two groups: 19 patients received osteopathic treatments (TG) and 12 patients received sham therapy (SG), both in four weekly sessions. Before the first and the last treatment, those patients were evaluated using Dizziness Handicap Inventory (DHI) and stabilometric platform to assess lifestyle modification and balance functions. After the treatment session, TG compared to SG showed an improvement in DHI global (p = 0.02), functional (p = 0.03) and physical (p = 0.03) components, as well as a reduction of swinging area (p = 0.02). An association between swinging area and lifestyle measures (global [r = 0.53; p = 0.02]; functional [r = 0.50; p = 0.03]; physical [r = 0.60; p = 0.01]) changes were found in TG. These findings suggest that OMT could be a useful approach to reduce imbalance symptoms and to improve the quality of life in patients suffering from dizziness.